Design and Validation of a Research Motivation Scale for Peruvian University Students (MoINV-U) - Esteban, Renzo Felipe Carranza; Mamani-Benito, Oscar; Huancahuire-Vega, Salomón; Lingan, Susana K. (Frontiers in Education, 2022)
The aim of the study was to design and validate a research motivation scale for Peruvian university students (MoINV-U). Instrumental design study where a scale of 16 items distributed in two factors (willingness and interest) was designed and validated. A total of 2,249 university students (59.2% women) participated in the study. To analyze the evidence of content-based validity, Aiken’s V coefficient was used; for construct validity, confirmatory factor analysis was used, and reliability was studied through Cronbach’s alpha coefficient. The items received a favorable evaluation (Aiken’s V > 0.70). The goodness-of-fit indices were adequate (CFI = 0.959, TLI = 0.950 and RMSEA = 0.080), likewise, the correlation between factor 1 and 2 was significant (p < 0.05), evidence of validity was obtained based on the relationship with other variables with measures of academic self-efficacy and academic procrastination and the reliability was acceptable (α = 0.87; 95% CI = 0.86–0.88). The MoINV-U scale is a tool that presents evidence of validity and reliability for the sample of Peruvian university students.